Introduction To Proofs PDF
Introduction To Proofs PDF
Introduction To Proofs PDF
• A proof is a valid argument that establishes the truth of a mathematical statement. A proof
can use the hypotheses of the theorem, if any, axioms assumed to be true, and previously
proven theorems. Using these ingredients and rules of inference, the final step of the proof
establishes the truth of the statement being proved.
Some Terminology:
• A theorem is a statement that can be shown to be true. Theorems can also be referred to as
facts or results.)
• A less important theorem that is helpful in the proof of other results is called a lemma.
• A corollary is a theorem that can be established directly from a theorem that has been
proved.
• A conjecture is a statement that is being proposed to be a true statement, usually on the
basis of some partial evidence, a heuristic argument, or the intuition of an expert. When a
proof of a conjecture is found, the conjecture becomes a theorem. Many times conjectures
are shown to be false, so they are not theorems.
Methods of Proving Theorems
• Direct Proofs: A direct proof of a conditional statement p → q is
constructed when the first step is the assumption that p is true;
subsequent steps are constructed using rules of inference, with the
final step showing that q must also be true. A direct proof shows that
a conditional statement p → q is true by showing that if p is true, then
q must also be true, so that the combination p true and q false never
occurs.
In a direct proof, we assume that p is true and use axioms, definitions,
and previously proven theorems, together with rules of inference, to
show that q must also be true.
Q. Give a direct proof of the theorem “If n is an odd integer, then n2 is odd.”
To begin a direct proof of this theorem, we assume that the hypothesis of this
conditional statement is true, namely, we assume that n is odd.
By the definition of an odd integer, it follows that n = 2k + 1, where k is some
integer. We want to show that n2 is also odd.
We can square both sides of the equation n = 2k + 1
n2 = (2k + 1)2 = 4k2 + 4k + 1 = 2(2k2 + 2k) + 1. By the definition of an
odd integer, we can conclude that n2 is an odd integer.
Consequently, we have proved that if n is an odd integer, then n2 is an odd
integer.
Q. Give a direct proof that if m and n are both perfect squares, then nm is also
a perfect square.
Assume that the hypothesis of this conditional statement is true, namely, we
assume that m and n are both perfect squares.
There are integers s and t such that m = s2 and n = t2.
Substituting s2 for m and t2 for n into mn.
mn = s2t2.
Hence, mn = s2t2 = (ss)(tt) = (st)(st) = (st)2, using commutativity and
associativity of multiplication.
We have proved that if m and n are both perfect squares, then mn is also a
perfect square.
Proof by Contraposition
• Direct proofs often reach dead ends. Unlike direct proofs, proofs that do not
start with the premises and end with the conclusion, are called indirect
proofs.
• Proof by Contraposition is a type of indirect proof. Proofs by contraposition
make use of the fact that the conditional statement p → q is equivalent to its
contrapositive, ¬q →¬p.
• This means that the conditional statement p → q can be proved by showing
that its contrapositive, ¬q →¬p, is true.
• In a proof by contraposition of p → q, we take ¬q as a premise, and using
axioms, definitions, and previously proven theorems, together with rules of
inference, we show that ¬p must follow.
Q. Prove that if 3n + 2 is odd, then n is odd where n is an integer.
Q. Show that the proposition P(0) is true, where P(n) is “If n > 1, then n2 > n”
and the domain consists of all integers.
P(0) is “If 0 > 1, then 02 > 0.” The hypothesis 0 > 1 is false. Using a vacuous proof,
P(0) is automatically true.
Trivial proof
We can also quickly prove a conditional statement p → q if we know that the
conclusion q is true. By showing that q is true, it follows that p → q must also be
true. A proof of p → q that uses the fact that q is true is called a trivial proof.
Q. Let P(n) be “If a and b are positive integers with a ≥ b, then an ≥ bn,” where
the domain consists of all nonnegative integers. Show that P(0) is true.
The proposition P(0) is “If a ≥ b, then a0 ≥ b0.” Because a0 = b0 = 1, the
conclusion of the conditional statement “If a ≥ b, then a0 ≥ b0” is true.
Hence, this conditional statement, which is P(0), is true. This is an example of a
trivial proof
Q3. Prove that the sum of two rational numbers is rational.
Let p be the proposition “At least four of 22 chosen days fall on the same day of
the week.”
Suppose that ¬p is true.
This means that at most three of the 22 days fall on the same day of the week.
Because there are seven days of the week, this implies that at most 21 days
could have been chosen, as for each of the days of the week, at most three of
the chosen days could fall on that day. This contradicts the premise that we
have 22 days under consideration. That is, if r is the statement that 22 days are
chosen, then we have shown that ¬p → (r ∧¬r).
Consequently, we know that p is true. We have proved that at least four of 22
chosen days fall on the same day of the week.
Rewriting a direct proof of p → q into proof by contradiction
In such proofs, we first assume that p and ¬q are true, and showing
that q must be also be true. This implies that ¬q and q are both true, a
contradiction.
Rewriting a proof by contraposition of a conditional statement as a proof by
contradiction.
In a proof of p → q by contraposition, we assume that ¬q is true. We
then show that ¬p must also be true. To rewrite a proof by contraposition of
p → q as a proof by contradiction, we suppose that both p and ¬q are true.
Then, we use the steps from the proof of ¬q →¬p to show that ¬p is true.
This leads to the contradiction p ∧¬p, completing the proof.
Q. Give a proof by contradiction of the theorem “If 3n + 2 is odd, then n is odd.”
Let p be “3n + 2 is odd” and q be “n is odd.”
To construct a proof by contradiction, assume that both p and ¬q are true. That
is, assume that 3n + 2 is odd and that n is not odd. Because n is not odd, we know
that it is even. Because n is even, there is an integer k such that n = 2k. This
implies that 3n + 2 = 3(2k) + 2 = 6k + 2 = 2(3k + 1).
Because 3n + 2 is 2t , where t = 3k + 1, 3n + 2 is even. Note that the statement “3n
+ 2 is even” is equivalent to the statement ¬p, because an integer is even if and
only if it is not odd. Because both p and ¬p are true, we have a contradiction.
This completes the proof by contradiction, proving that if 3n + 2 is odd, then n is
odd.
Mistakes in Proofs
What is wrong with this famous supposed “proof” that 1 = 2?
We use these steps, where a and b are two equal positive integers.
Step Reason
1. a = b Given
2. a2 = ab Multiply both sides of (1) by a
3. a2 − b2 = ab − b2 Subtract b2 from both sides of (2)
4. (a − b)(a + b) = b(a − b) Factor both sides of (3)
5. a + b = b Divide both sides of (4) by a − b
6. 2b = b Replace a by b in (5) because a = b and simplify
7. 2 = 1 Divide both sides of (6) by b
• Many incorrect arguments are based on a fallacy called begging the question.
This fallacy occurs when one or more steps of a proof are based on the truth
of the statement being proved. This fallacy arises when a statement is proved
using itself, or a statement equivalent to it. That is why this fallacy is also
called circular reasoning.
• Suppose that n2 is even. Then n2 = 2k for some integer k. Let n = 2l for some
integer l. This shows that n is even.
This argument is incorrect. The statement “let n = 2l for some integer l” occurs
in the proof. This is circular reasoning because this statement is equivalent to
the statement being proved, namely, “n is even.”
PROOFS OF EQUIVALENCE
To prove a theorem that is a biconditional statement, that is, a statement of the
form p ↔ q, we show that p → q and q → p are both true.
(p ↔ q) ≡ (p → q) ∧ (q → p).
Let p: n is odd
q: n2 is odd
(p ↔ q) ≡ (p → q) ∧ (q → p).
We need to show, (p → q) and (q → p) are T.
Trying using direct proof for (p → q) Trying using proof by C.P. for (q → p)
Assume p is T. Assume ¬p is T.
n=2k+1, where k is an integer. n is even, n=2k, where k is an integer
Squaring both sides Squaring both sides
n2 = 4k2+4k+1 n2 = 4k2
n2 = 2(2k2+2k)+1 n2 = 2(2k2)
n2 = 2(k’)+1, where k’=2k2+2k n2 is even, i.e. ¬ q is T.
n2 is odd, i.e. q is T.
By direct proof, (p → q) is T By proof by C.P. (q → p) is T
Q1. Show that these statements about the integer n are equivalent:
p1: n is even.
p2: n − 1 is odd.
p3: n2 is even.
Show that these three statements are equivalent by showing that the
conditional statements p1 → p2, p2 → p3, and p3 → p1 are true.
Q. Use a direct proof to show that the sum of two odd integers is even.
p: Let m and n be two odd integers.
q: Sum of two odd integers is even.
Let p is T
m=2k+1, where k is an integer.
n=2l+1 , where l is an integer.
Adding m and n,
m + n = (2k+1) + (2l+1)
= 2(k+l+1)
=2k’, where k’= k+l+1
i.e. m + n is even, q is T
Q. Use a direct proof to show that every odd integer is the difference of two
squares.
P(x): x is an odd integer.
Q(x): x is the difference of two squares.
Assume P(x) is T.
x = 2k+1
= k2 + 2k + 1 - k2
= (k+1)2 – k2
Q. Prove that if n is a perfect square, then n + 2 is not a perfect square.
p: n is a perfect square.
q: n + 2 is not a perfect square
Assume n=b2
Using proof by contradiction.
Assume p and ¬ q is T,
If n is a perfect square, there exist an integer x such that,
n=x2
If n+2 is a perfect square, there exist an integer y such that,
n+2=y2
x2+2=y2
2=y2-x2
2=(y+x)(y-x)
The only possible integers are 1 and 2
y+x=2 and y-x=1 or y+x=1 and y-x=2
Adding we get, 2y=3 or y=3/2, which contradicts that y is an integer. The assuming that n+2 is
perfect square is incorrect.
Hence, n + 2 is not a perfect square
Q. Use a proof by contradiction to prove that the sum of an irrational number
and a rational number is irrational.
To prove: x+y=z, where x is irrational, y is rational and z is irrational.
Using proof by contradiction
Assume, sum of an irrational number and a rational number is rational.
y=a/b and z=c/d, where b and d ≠ 0
x+a/b=c/d
x=c/d-a/b
x=(cb-ad)/bd
We can say x is rational, which contradicts x is irrational.
So, our assumption that sum of an irrational number and a rational number is
rational is incorrect.
Hence, sum of an irrational number and a rational number is irrational.
Q. Prove that if m and n are integers and mn is even, then m is even or n is even.
p: mn is even.
q: m is even or n is even.
Using proof by contradiction
Assume p and ¬ q is T,
¬ q : m is odd and n is odd.
m=2k+1 and n=2l+1
mn =(2k+1)(2l+1)
= 4kl+2k+2l+1
=2(2kl+k+l)+1
= 2k’+1, where k’=(2kl+k+l)
i.e. mn is odd which contradicts p.
Hence, using proof by contradiction, if m and n are integers and mn is even, then m is
even or n is even.
Q2. Show that if n is an integer and n3 + 5 is odd, then n is even using
a) a proof by contraposition.
b) a proof by contradiction.
Q3. Show that at least ten of any 64 days chosen must fall on the same day of
the week.
Q. Use a proof by contradiction to show that there is no rational number r for which r3 + r + 1 =
0.
Assume that r = a/b is a root, where a and b are integers and a/b is in lowest terms.
(a/b)3 + (a/b) + 1 = 0
a3/b3 + a/b + 1 = 0
( a3+ab2+b3 ) /b3=0 a b a3+ab2+b3
a3+ab2+b3=0 Odd Odd Odd + Odd + Odd = Odd
Odd Even Odd + Even + Even = Odd
Even Odd Even + Even + Odd = Odd
Even Even Even + Even + Even = Even
Only when a and b are even, 0 can be obtained, which means a/b is not in lowest terms.
Our assumption is wrong.
Hence, there is no rational number r for which r3 + r + 1 = 0.
Q. Prove that at least one of the real numbers a1, a2, . . . , an is greater than or
equal to the average of these numbers. What kind of proof did you use?
Q. Prove that at least one of the real numbers a1, a2, . . . , an is greater than or equal to the
average of these numbers. What kind of proof did you use?
p: At least one of the real numbers a1, a2, . . . , an is greater than or equal to the average of
these numbers.
Assume ¬p is T.
¬p: None of the real numbers a1, a2, . . . , an is greater than or equal to the average of these
numbers.
a1<(a1+a2+…+an)/n (1)
a2<(a1+a2+…+an)/n (2)
.
.
an<(a1+a2+…+an)/n (n)
Adding, a1+a2+…+an<1/n{n(a1+a2+…+an)}
a1+a2+…+an<(a1+a2+…+an) which is a contradiction.
Our assumption is wrong.
Hence, At least one of the real numbers a1, a2, . . . , an is greater than or equal to the average
of these numbers.
Proof by Cases
Sometimes we cannot prove a theorem using a single argument that holds for all
possible cases.
To prove a conditional statement of the form
(p1 ∨ p2 ∨ · · · ∨ pn) → q
the tautology
[(p1 ∨ p2 ∨ · · · ∨ pn) → q] ↔ [(p1 → q) ∧ (p2 → q) ∧ · · · ∧ (pn → q)]
can be used as a rule of inference.
This shows that the original conditional statement with a hypothesis made up of a
disjunction of the propositions p1, p2, . . . , pn can be proved by proving each of the n
conditional statements pi → q, i = 1, 2, . . . , n, individually. Such an argument is called
a proof by cases.
EXHAUSTIVE PROOF
Some theorems can be proved by examining a relatively small number of examples.
Such proofs are called exhaustive proofs, or proofs by exhaustion because these
proofs proceed by exhausting all possibilities.
Q. Prove that (n + 1)3 ≥ 3n if n is a positive integer with n ≤ 4.
We use a proof by exhaustion. We only need verify the inequality (n + 1)3 ≥ 3n
when n = 1, 2, 3, and 4.
For n = 1, we have (n + 1)3 = 23 = 8 and 3n = 31 = 3;
for n = 2, we have (n + 1)3 = 33 = 27 and 3n = 32 = 9;
for n = 3, we have (n + 1)3 = 43 = 64 and 3n = 33 = 27;
and for n = 4, we have (n + 1)3 = 53 = 125 and 3n = 34 = 81.
In each of these four cases, we see that (n + 1)3 ≥ 3n. We have used the method of
exhaustion to prove that (n + 1)3 ≥ 3n if n is a positive integer with n ≤ 4.
Q. Prove that if n is an integer, then n2 ≥ n.
We can prove that n2 ≥ n for every integer by considering three cases, when n
= 0, when n ≥ 1, and when n ≤ −1. We split the proof into three cases zero,
positive integers, and negative integers separately.
Case (i): When n = 0, because 02 = 0, we see that 02 ≥ 0. It follows that n2 ≥ n is
true in this case.
Case (ii): When n ≥ 1, when we multiply both sides of the inequality n ≥ 1 by
the positive integer n, we obtain n · n ≥ n · 1. This implies that n2 ≥ n for n ≥ 1.
Case (iii): In this case n ≤ −1. However, n2 ≥ 0. It follows that n2 ≥ n.
Because the inequality n2 ≥ n holds in all three cases, we can conclude that if n
is an integer, then n2 ≥ n.
Proof Strategies
Forward reasoning
direct proof and indirect proof
Backward reasoning
Unfortunately, forward reasoning is often difficult to use to prove
more complicated results, because the reasoning needed to reach the
desired conclusion may be far from obvious. In such cases it may be
helpful to use backward reasoning. To reason backward to prove a
statement q, we find a statement p that we can prove with the
property that p → q.
Q. Given two positive real numbers x and y, their arithmetic mean is (x + y)/2 and their geometric
mean is √xy. When we compare the arithmetic and geometric means of pairs of distinct positive real
numbers, we find that the arithmetic mean is always greater than the geometric mean. Prove that this
inequality is always true?
To prove that (x + y)/2 >√xy when x and y are distinct positive real numbers,
we can work backward. We construct a sequence of equivalent inequalities. The equivalent
inequalities are:
(x + y)/2 >√xy
(x + y)2/4 > xy, (Squaring)
(x + y)2 > 4xy
x2 + 2xy + y2 > 4xy
x2 − 2xy + y2 > 0
(x − y)2 > 0
Because (x − y)2 > 0 when x ≠ y, it follows that the final inequality is true.
Once we have carried out this backward reasoning, we can easily reverse the steps to construct a proof
using forward reasoning. We now give this proof.
Suppose that x and y are distinct positive real numbers.
Then (x − y)2 > 0
….
Q. Suppose that two people play a game taking turns removing one, two, or three stones
at a time from a pile that begins with 15 stones. The person who removes the last stone
wins the game. Show that the first player can win the game no matter what the second
player does.
To prove that the first player can always win the game, we work backward.
INDUCTIVE STEP: The inductive hypothesis is the statement that P(k) is true, where k is an arbitrary nonnegative integer. That is, P(k) is
the statement that
𝑎𝑟 𝑘+1 −𝑎
𝑎 + 𝑎𝑟 + 𝑎𝑟2 + ⋯ + 𝑎𝑟𝑘 = 𝑟−1
𝑎𝑟 𝑘+2 −𝑎
To prove: 𝑎 + 𝑎𝑟 + 𝑎𝑟2 + ⋯ + 𝑎𝑟𝑘 + 𝑎𝑟 𝑘+1 =
𝑟−1
L.H.S.
𝑎𝑟 𝑘+1 −𝑎
𝑎 + 𝑎𝑟 + 𝑎𝑟2 + ⋯ + 𝑎𝑟𝑘 + 𝑎𝑟 𝑘+1 = + 𝑎𝑟 𝑘+1
𝑟−1
𝑎𝑟 𝑘+1 −𝑎 +𝑎𝑟 𝑘+1 (𝑟−1)
= 𝑟−1
𝑎𝑟 𝑘+1 −𝑎 +𝑎𝑟 𝑘+2 −𝑎𝑟 𝑘+1
=
𝑟−1
𝑎𝑟 𝑘+2 −𝑎
= 𝑟−1
= 𝑅. 𝐻. 𝑆.
This shows that if the inductive hypothesis P(k) is true, then P(k + 1) must also be true. This completes the inductive argument.
PROVING INEQUALITIES
Q. Use mathematical induction to prove the inequality n < 2n for all positive integers n.
Let P(n) be the proposition that n < 2n.
BASIS STEP: P(1) is true, because 1 < 21 = 2. This completes the basis step.
INDUCTIVE STEP: We first assume the inductive hypothesis that P(k) is true for an
arbitrary positive integer k. We need to show that if k < 2k, then k + 1 < 2k+1.
Adding 1 on both side of P(k)
k+1 < 2k + 1
k+1 < 2k + 1 ≤ 2k + 2k = 2 · 2k = 2k+1. Since 1 ≤ 2k
This shows that P(k + 1) is true, namely, that k + 1 < 2k+1, based on the assumption that
P(k) is true. The induction step is complete. Therefore, because we have completed
both the basis step and the inductive step, by the principle of mathematical induction
we have shown that n < 2n is true for all positive integers n.
Q. Use mathematical induction to prove that 2n < n! for every integer n
with n ≥ 4. (Note that this inequality is false for n = 1, 2, and 3.)
Q. Use mathematical induction to prove that 2n < n! for every integer n with n
≥ 4. (Note that this inequality is false for n = 1, 2, and 3.)
Let P(n) be the proposition that 2n < n!.
BASIS STEP: To prove the inequality for n ≥ 4 requires that the basis step be P(4). Note that
P(4) is true, because 24 = 16 < 24 = 4!
INDUCTIVESTEP: For the inductive step, we assume that P(k) is true for an arbitrary integer k
with k ≥ 4. We must show that if 2k < k! for an arbitrary positive integer k where k ≥ 4, then
2k+1 < (k + 1)!.
2k+1 = 2 · 2k
< 2 · k! (by the inductive hypothesis)
< (k + 1)k! (since 2 < k + 1)
< (k + 1)!
This shows that P(k + 1) is true when P(k) is true. This completes the inductive step of the
proof.
PROVING DIVISIBILITY RESULTS
Q. Use mathematical induction to prove that n3 − n is divisible by 3 whenever n is a
positive integer.
To construct the proof, let P(n) denote the proposition: “n3 − n is divisible by 3.”
BASIS STEP: The statement P(1) is true because 13 − 1 = 0 is divisible by 3. This
completes the basis step.
INDUCTIVE STEP: For the inductive hypothesis we assume that P(k) is true; that is, we
assume that k3 − k is divisible by 3 for an arbitrary positive integer k.
We must show that (k + 1)3 − (k + 1) is divisible by 3.
(k + 1)3 − (k + 1) = (k3 + 3k2 + 3k + 1) − (k + 1)
= (k3 − k) + 3(k2 + k).
= Divisible by 3 from P(k) + Multiple of 3
= Divisible by 3.
Because we have completed both the basis step and the inductive step, by the
principle of mathematical induction we know that n3 − n is divisible by 3 whenever n
is a positive integer.
Q. Use mathematical induction to prove that 7n+2 + 82n+1 is divisible by 57 for
every nonnegative integer n.
Strong Induction
STRONG INDUCTION
To prove that P(n) is true for all positive integers n, where P(n) is a
propositional function, we complete two steps:
BASIS STEP: We verify that the proposition P(1) is true.
INDUCTIVE STEP: We show that the conditional statement [P(1) ∧ P(2) ∧ · · · ∧
P(k)] → P(k + 1) is true for all positive integers k.
When we use strong induction to prove that P(n) is true for all positive integers
n, our inductive hypothesis is the assumption that P(j) is true for j = 1, 2, . . . , k.
That is, the inductive hypothesis includes all k statements P(1), P(2), . . . , P (k).
Because we can use all k statements P(1), P(2), . . . , P (k) to prove P(k + 1), rather
than just the statement P(k) as in a proof by mathematical induction, strong
induction is a more flexible proof technique.
Q. Show that if n is an integer greater than 1, then n can be written as the product of primes.
Let P(n) be the proposition that n can be written as the product of primes.
BASIS STEP: P(2) is true, because 2 can be written as the product of one prime, itself.
INDUCTIVE STEP: The inductive hypothesis is the assumption that P(j) is true for all integers j
with 2 ≤ j ≤ k, that is, the assumption that j can be written as the product of primes whenever
j is a positive integer at least 2 and not exceeding k.
To complete the inductive step, it must be shown that P(k + 1) is true under this assumption,
that is, that k + 1 is the product of primes.
There are two cases to consider, namely, when k + 1 is prime and when k + 1 is composite.
If k + 1 is prime, we immediately see that P(k + 1) is true.
Otherwise, k + 1 is composite and can be written as the product of two positive integers a
and b with 2 ≤ a ≤ b < k + 1. Because both a and b are integers at least 2 and not exceeding k,
we can use the inductive hypothesis to write both a and b as the product of primes. Thus, if k
+ 1 is composite, it can be written as the product of primes, namely, those primes in the
factorization of a and those in the factorization of b.